2007
DOI: 10.1007/s00259-006-0297-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dose distributions in solid tumors from 186Re transported by liposomes using HS radiochromic media

Abstract: The described procedures and techniques have shown the potential and utility of HS GafChromic film for determination of dose rate distributions in solid tumors injected intratumorally with 186Re-liposomes. The film's structure and the liposomes' biodistribution must be taken into account to obtain quantitative dose measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Radiance before and after tumor insonation with systemic and intratumoral injection is quantified. While systemic injection is desirable, local injection and activation provide an opportunity to increase drug concentration and assess release from the capsule [30, 31]. …”
Section: Introductionmentioning
confidence: 99%
“…Radiance before and after tumor insonation with systemic and intratumoral injection is quantified. While systemic injection is desirable, local injection and activation provide an opportunity to increase drug concentration and assess release from the capsule [30, 31]. …”
Section: Introductionmentioning
confidence: 99%
“…This study showed that an EUD model incorporating dose heterogeneity in a tumour would be helpful in predicting responses from radiation nanomedicines. Medina et al ( 2007 ) described a method to visually and digitally show the spatial dose distribution in a tumour following i.t. injection of [ 186 Re]Re-BMEDA-liposomes (122 nm) in rats with s.c. SCC-4 human head and neck squamous cell carcinoma tumours.…”
Section: Main Textmentioning
confidence: 99%
“…Los liposomas son vesículas de dimensiones nanométricas formadas por una doble capa de fosfolípidos que encierran un espacio acuoso. Existen algunos estudios dosimétricos tanto teóricos [6,7] como experimentales [8,9] , así como algunos estudios preclínicos [10,11] que analizan el uso de complejos liposoma-radionúclido con nes terapéuticos, administrados por vía intravenosa o intratumoral en tumores sólidos. En el caso intratumoral, se ha encontrado que es ventajoso el mayor grado de localización y jación obtenido mediante la inyección directa en el tumor de los liposomas radiactivos, lo que se traduce en una dosis de radiación mayor en el tumor y menor en los tejidos sanos, así como una relajación del requisito de una distribución homogénea en todo el tumor debido al efecto de fuego cruzado de la radiación [12] ; a pesar de esto, la correcta determinación de la biodistribución de los liposomas radiactivos dentro del tejido tumoral sigue siendo un factor preponderante en la determinación de la distribución espacial de la dosis [8] .…”
Section: Introductionunclassified